2011
DOI: 10.1111/j.1365-2834.2011.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of managers’ turnover and health in a healthcare organization

Abstract: Healthcare organizations should focus not only on developing individuals in their managerial role but also on strengthening the conditions that allow managers to exercise their leadership and to ensuring that the managers most suitable for their posts do not leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 62 publications
1
45
0
2
Order By: Relevance
“…External assessments of the working conditions can be valuable in validating other qualitative as well as quantitative results, especially among managers that repeatedly have shown to underestimate unadvantagous work situations and ill-health (e.g., Skagert et al, 2012). Furthermore, in order to avoid over-reporting of unfavorable work characteristics among those with psychological distress, it is preferable to use methods that aim to distinguish the actual conditions from the individual's emotional response to them (Waldenström et al, 2008).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…External assessments of the working conditions can be valuable in validating other qualitative as well as quantitative results, especially among managers that repeatedly have shown to underestimate unadvantagous work situations and ill-health (e.g., Skagert et al, 2012). Furthermore, in order to avoid over-reporting of unfavorable work characteristics among those with psychological distress, it is preferable to use methods that aim to distinguish the actual conditions from the individual's emotional response to them (Waldenström et al, 2008).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Recent evidence from the human service sector points to a troublesome work situation, and to the problems of attracting and retaining skilled managers (Arman et al, 2009;Corin et al, 2016;Danielson et al, 2012;Höckertin, 2007;Skagert et al, 2012). First-line managers of human service organizations are particularly exposed and in disadvantageous work situations (e.g., Berntson et al, 2012;Björk, 2013).…”
mentioning
confidence: 99%
“…Also, self-rated health and work attendance had increased among their employees, as measured by employee questionnaires [28]. However, the health and working conditions of the managers themselves had not improved, and there were several indications of more stress, and stressful work conditions among managers [17][18][19]29,30], in addition to high turnover rates [31] for managers in the public sector. These challenges were often associated with the demands of organizational restructurings and continuous workplace changes [17,30,32].…”
Section: Development Of a Theoretical Framework And Leadership Programmentioning
confidence: 99%
“…According to Skagert, Dellve, Eklöf, Pousette and Ahlborg (2008) and Skagert, Dellve and Ahlborg (2012), the most common perceived stressors among Healthcare managers are the following: unclear expectations, conflicts of legitimacy, conflicts regarding objectives, value conflicts and loneliness.…”
Section: Swedish Healthcare Managers and The Media -A Study Of Stratementioning
confidence: 99%
“…This management model emphasises the importance of personal responsibility among Healthcare managers. Skagert, Dellve and Ahlborg (2012) conducted a study that showed that among Healthcare managers 40 percent had resigned from their management position within a four-year period. Similar results were presented in a study performed by Stengård (2013) concerning municipal care services, where 20 percent of the managers had resigned within a two-year period.…”
mentioning
confidence: 99%